Optical inspection of photomasks: What's next? - Brooks, George W. (SPIE, 2023)
The subject of photomask inspection has received increasing attention over the past few years. Mask makers have come to rely on automatic optical inspection for two reasons. First, it is a necessary means to provide quality assurance to their fabline customers. The fablines will specify a maximum defect dimension and a maximum defect density. These specifications can be guaranteed. Second, photomask inspection is a vital link in control of the mask making process itself. The feedback provides excellent information on raw material inputs (i.e., chrome, glass, and resist), on the lithography process, and on handling and cleanliness in the mask shop.